Enhancing the dynamic performance of electricity production in steam power plants by the integration of transient waste heat sources into the feed-water pre-heating system. (5th April 2005) - Roth, K.; Scherer, V.; Behnke, K.
Since the deregulation of the energy market the enhancement of steam power plant's dynamic performance has become more and more important. Nowadays, peak load is a profitable product at the energy stock markets if it can be provided reliably. This is in contrast to many power plants running constantly at full load. A very promising technique to improve the peak load capability of such power plants is to integrate transient external waste heat sources into the cycle. Feed-water pre-heaters are one favourable location to integrate the external heat into the water steam cycle. Since the addition of the external energy causes less steam consumption in the high-pressure and low-pressure pre-heaters, one or more steam extraction lines can be closed. By doing this, the steam can be used for additional power generation in the steam turbine. The analysis of the occurring time-dependent processes are studied on a numerical basis, using the dynamic process simulation software APROS from VTT. With APROS, a comprehensive power plant model of a fossil-fuelled conventional steam power plant with an output of 393 MW was built, adapted and parameterised. In the simulations two different kinds of external heat sources have been integrated into the cycle: a fast-starting gas turbine and an industrial steam line. The simulation results show a fast steam turbine power increase of 32 MW within less than 14 minutes in both the cases. Adding the power output of the gas turbine, an additional 118 MW is provided accompanied by a 2% efficiency increase of the entire plant. This means less consumption of fossil fuels and consequently a significant reduction of CO2 and other pollutants.